Student-lecturer interactions: Do traditional methods appeal to Generation Z students? - Adriaan Lochner Lochner (Perspectives in Education)
Higher education institutions have various and mostly well-established methods for students to consult with their lecturers. Lecturers have traditionally expected students to make use of face-to-face interaction through after-class consultations and asking questions in class. It is, however, imperative that higher education reflects on whether these traditional consultation methods appeal to today’s students where there is a generational differential between the lecturer and the student who is part of Generation Z. Generational differences include the integration of technology, such as access to the Internet and various other technological platforms for communication on a variety of social media applications. As such, it is important for lecturers to understand why a student might not be comfortable with traditional interaction methods and must take into consideration student feedback in creating opportunities for interaction that considers the needs of all stakeholders. This study, following a qualitative deductive approach, used online questionnaires to obtain students’ perceptions of both the potential shortcomings and advantages of a variety of consultation methods available to them at a residential university in South Africa. This variety included the incorporation of technology into consultation methods in contrast to a traditional consultation. The questionnaire was formulated using Rolfe, Freshwater and Jasper’s (2001) reflection model and grounded in attribution theory, whereby student-lecturer interaction methods were analysed. The findings of the study show that students will engage with a lecturer if they feel the lecturer is approachable and helpful, regardless of the nature of the consultation method. Lecturers can invest in improving their soft skills to enhance being perceived as approachable by students. The findings also highlight that the method of interaction may cause anxiety and that students sometimes feel too overwhelmed to ask the lecturer for help. The students suggested consultation methods that provide a quick turnaround time and are easy to use (for example, being in a WhatsApp group with their lecturer). The findings of this study provide insight that higher education institutions and lecturers can use to improve students’ usage of student-lecturer interaction methods.